A new turn-on fluorescent probe for selective detection of glutathione and cysteine in living cells - Wei, Mingjie; Yin, Peng; Shen, Youming; Zhang, Lingli; Deng, Jianhui; Xue, Shanyan; Li, Haitao; Guo, Bin; Zhang, Youyu; Yao, Shouzhuo (Chemical communications (Cambridge, England), 2013)
A fluorescent probe (N-(4-methyl-2-oxo-2H-chromen-7-yl)-2,4-dinitrobenzenesulfonamide), which exhibits high selectivity to glutathione and cysteine among amino acids including sulphur-containing methionine and metal ions, was synthesized. The experiments demonstrate that the fluorescent probe is a reliable and specific probe for glutathione and cysteine in living cells.